A shape memory alloy rod element based on the co-rotational formulation for nonlinear static analysis of tensegrity structures. (January 2017) - Faroughi, Shirko; Haddad Khodaparast, Hamed; Friswell, Michael I; Hosseini, Seyed Hamed
In this article, a shape memory alloy rod element is derived based on the co-rotational formulation. In the co-rotational approach, the rigid body modes are removed from the total deformations by employing a local coordinate system at element level, and hence, the major part of geometric nonlinearity is isolated. The linear shape memory alloy rod element is developed using a shape memory alloy constitutive model together with the small strain framework employed by the co-rotational approach. The one-dimensional shape memory alloy model is adopted to calculate both the pseudo-elastic response and the shape memory effects. The new formulation is exploited to perform static analysis of tensegrity structures in order to study the accuracy and robustness of the proposed element and its capability to describe the structural response of shape memory alloy devices.